Difficulties in implementing “Ki Hadjar Dewantara's Tamansiswa teachings” on vocational education - Rabiman Rabiman; Dianna Ratnawati; Endang Wani Karyaningsih (Universitas Negeri Yogyakarta, 2022)
This study aimed to describe the difficulties of vocational education teachers in applying the teachings of Tamansiswa Ki Hadjar Dewantara (KHD) method in the learning process. This study used the descriptive qualitative approach that was chosen to reveal the existing phenomena based on the perspectives of 12 vocational education teachers. The data collection techniques used in-depth interviews and observation. The study results reveal that teachers still limit the teachings of Tamansiswa KHD. All teachers only know the basics of concepts, and even then, they cannot elaborate more deeply on the concepts of the teachings. The teacher admitted that it was difficult to apply the teachings during the learning process and received confirmation directly from the results of observations, which found no teaching activity for Tamansiswa KHD during the learning process and in the teachers' plan. Various socialization and training are needed to provide a comprehensive understanding for teachers in applying these teachings in learning so that their character values can be reflected in students.